2008
DOI: 10.21273/jashs.133.5.670
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Copper Toxicity in Arabidopsis thaliana by Silicon Addition to Hydroponic Solutions

Abstract: Copper (Cu) is an essential micronutrient for plants and is the a.i. in pesticides for some pathogens and algae. Elevated doses of Cu can cause toxicity in plants. While silicon (Si) is reported to alleviate the toxicity of some heavy metals, its role in reducing the symptoms induced by excess Cu is unclear. Therefore, the role of Si in plant response to Cu stress was investigated in arabidopsis [Arabidopsis thaliana (L.) Heyn.]. Based on plant symptoms (a reduction of leaf c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 38 publications
(42 reference statements)
4
40
1
3
Order By: Relevance
“…2) and, as a result, plants growth and biomass was decreased in B. napus. Earlier studies showed that 30 mM Cu in hydroponic decreased root growth and caused leaf chlorosis in Arabidopsis thaliana (Li et al, 2008) while, 7.5 mM Cu can cause upto 50% reduction in root of biomass maize (Ouzounidou et al, 1995). However, the degree of damage to the growth of B. napus as observed in the present study is relatively low, which indicated a level of Cu stress tolerance in this plant.…”
Section: Effect Of Copper On Plant Morphology and Compositioncontrasting
confidence: 58%
“…2) and, as a result, plants growth and biomass was decreased in B. napus. Earlier studies showed that 30 mM Cu in hydroponic decreased root growth and caused leaf chlorosis in Arabidopsis thaliana (Li et al, 2008) while, 7.5 mM Cu can cause upto 50% reduction in root of biomass maize (Ouzounidou et al, 1995). However, the degree of damage to the growth of B. napus as observed in the present study is relatively low, which indicated a level of Cu stress tolerance in this plant.…”
Section: Effect Of Copper On Plant Morphology and Compositioncontrasting
confidence: 58%
“…TMV was resuspended in sodium phosphate buffer (pH 7.0), mixed with washed celite and used for inoculum. N. tabacum seeds were germinated hydroponically in nutrient solution containing 0.1 mM soluble K 2 SiO 3 as described by Li et al (2008). Plants were hydroponically propagated in a growth chamber at 20 • C under a 16 h light: 8 h dark photoperiod at a light intensity of 70 mol m −2 s −1 of photosynthetically active radiation.…”
Section: Propagation Of Viruses and N Tabacum Plantsmentioning
confidence: 99%
“…These authors suggested that the formation of Zn-silicate compounds in the cytoplasm may be responsible for the alleviation of the Zn toxicity. In Arabidopsis thaliana, Li et al (2008) have shown that Si improves the resistance to Cu stress. A recent study has shown that Si modulates the expression of various genes involved in Cu tolerance in A. thaliana (Khandekar and Leisner 2011).…”
Section: Interactions Between Metals and Simentioning
confidence: 99%